Biotechnological interventions in food waste treatment for obtaining valuea‘added compounds to combat pollution - Sreekala, Aparna Ganapathy Vilasam; Ismail, Muhammad Heikal; Nathan, Vinod Kumar (Springer, 2022)
Over the last few decades, the globe is facing tremendous effects due to the unnecessary piling of municipal solid waste among which food waste holds a greater portion. This practice not only affects the environment in terms of generating greenhouse gas emissions but when left dumped in landfills will also trigger poverty and malnutrition. This review focuses on the global trend in food waste management strategies involved in the effective utilization of food waste to produce various value-added products in a microbiology aspect, thereby diminishing the negative impacts caused by the unnecessary side effects of non-renewable energy sources. The review also detailed the efficiency of microorganisms in the production of various bio-energies as well. Further, recent attempts to the exploitation of genetically modified microorganisms in producing value-added products were enlisted. This also attempted to address food waste valorization techniques, the combined applications of various processes for an enhanced yield of different compounds, and addressed various challenges. Further, the current challenges involved in various processes and the effective measures to tackle them in the future have been addressed. Thus, the present review has successfully addressed the circular bio-economy in food waste valorization.